The Effects of Use of Learning Strategies Training on Students Foreign Language Vocabulary Learning - Fallahchai, Seyed Reza (EDUCARE, 2012)
ABSTRACT: Foreign language vocabulary learning, in this case is English, is not the same as memorizing words in the context of serial lists. To master a foreign language, words must be recalled and recognized in new and unexpected contexts. The paper describes a research project which investigated how vocabulary can best be learned or taught with 558 primary (6th grade) Â students (four groups of from sixteen intact classes). Four approaches to vocabulary instruction: (1) Vocal rehearsal + phonological awareness training; (2) Sub-vocal rehearsal + phonological awareness training; (3) Vocal and sub-vocal rehearsal + phonological awareness training; and (4) No rehearsal and phonological awareness training were examined in this study and a comparison was made of their effects on students vocabulary acquisition. Pre-test and post-test vocabulary knowledge scales were administrated and an ANOVA analyses was conduct to identify any significant difference among four groups. The results indicate that all three methods resulted in significant vocabulary gains. Furthermore, the difference between first group, vocal rehearsal phonological awareness training; and second group, sub-vocal rehearsal phonological awareness training, was not significant; participants in the third group did significantly better than those.KEY WORDS: Learning strategies, rehearsal, phonological awareness, foreign language, teaching vocabulary, and English as second language.===About the Author: Dr. Seyed Reza Fallahchai is Assistant Professor of Psychology at the Department of Psychology HU (Hormozgan University), P.O. Box 3995, Bandar Abbas, Iran. He can be reached at: rfallahchai@yahoo.comHow to cite this article? Fallahchai, Seyed Reza. (2012). âThe Effects of Use of Learning Strategies Training on Students Foreign Language Vocabulary Learningâ in EDUCARE: International Journal for Educational Studies, Vol.5(1) August, pp.25-38. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 20, 2012); Revised (July 30, 2012); and Published (August 17, 2012).